Local ecological knowledge on preferred vegetation of African savanna elephants in the semi-desert highlands of northwest Namibia - Michael Wenborn; Vincent Nijman; Ash Parton; Magdalena S. Svensson; Aho N. Nashongo; Morgan Hauptfleisch (Journal of Arid Environments, 2025)

Correction: Reflecting Experiences of Regional Academic, Tourism, and Education Specialists in Geoheritage Evaluation for Fujairah, UAE and Southeast Arabia - Kenta Sayama; Adrian G Parker; Ash Parton; Heather Viles (Geoheritage, 2024)

Reflecting Experiences of Regional Academic, Tourism, and Education Specialists in Geoheritage Evaluation for Fujairah, UAE and Southeast Arabia - Kenta Sayama; Adrian G Parker; Ash Parton; Heather Viles (Geoheritage, 2024)
In Southeast Arabia (i.e. the United Arab Emirates [UAE] and Oman), geoconservation is a budding initiative, but to date, there has been limited evaluation of geoheritage sites in this region. Many geoheritage evaluation methods have been developed over the last 20 years, but the most popular methods reflect experiences from experts in Europe. The representativeness of these methods for different regional, cultural, and social contexts requires scrutiny. This study developed the first parametric method for geoheritage evaluation focused on Southeast Arabia, using Fujairah, UAE as a case study. The study applied a novel approach based on questionnaires completed by regional geoscience academics, local nature tourism professionals, and local science teachers. The preferences they expressed for scientific value, educational value, and touristic value, respectively, were used to develop the evaluation method. To test the requirements for informed decisions by tourism professionals and science teachers, the study compared results of questionnaires from two occasions: after a seminar on regional geoheritage sites, and after site visits. The resulting method deviates from previous methods in the relative weight it places on various criteria, substantiating the need to target wider regional voices in methods for geoheritage evaluation in Fujairah and Southeast Arabia. It reflects the need to consider cultural and societal differences, as well as curricular requirements for the educational value, that are not highlighted in existing evaluation methods. The applicability of the method was tested and confirmed by ranking geosites in Fujairah, and the method could be used at a regional scale in the future.

The aggradation of alluvial fans in response to monsoon variability over the last 400 ka in the Hajar Mountains, south-east Arabia - Sam Woor; David S.G. Thomas; Julie A. Durcan; Sallie L. Burrough; Ash Parton (Quaternary Science Reviews, 2023)

Morphology and controls of the mountain-front fan systems of the Hajar Mountains, south-east Arabia - Sam Woor; David S.G. Thomas; Ash Parton; Anya Leenman (Earth-Science Reviews, 2023)

Human occupation of the northern Arabian interior during early Marine Isotope Stage 3 - Richard P. Jennings; Ash Parton; Laine Clark‐Balzan; Tom S. White; Huw S. Groucutt; Paul S. Breeze; Adrian G. Parker; Nick A. Drake; Michael D. Petraglia (Journal of Quaternary Science, 2016)
The early part of Marine Isotope Stage (MIS) 3 (ca. 60–50 ka) is a crucial period for studying human demography and behaviour in south‐west Asia, and how these relate to climatic changes. However, the archaeological and palaeoenvironmental records for MIS 3 in critical areas such as the Arabian Peninsula remain poorly developed. Here, we present findings from the Al Marrat basin in the Nefud desert, which provides the first clear evidence for both increased humidity and human occupation of the interior of northern Arabia during early MIS 3. A Middle Palaeolithic assemblage, dated by optically stimulated luminescence to ca . 55 ka, was found stratified within a sequence of relict palustrine deposits indicative of shallow water body formation in the Al Marrat basin. Hominin presence in northern Arabia at this time coincides with the intensification and northward displacement of monsoon rainfall systems during a period of maximum insolation. These findings add to a growing corpus of palaeoenvironmental evidence, which indicates that the Arabian interior was neither arid nor unpopulated during early MIS 3, and that hydrodynamic responses to enhanced moisture availability facilitated demographic expansions into the Arabian interior.

Low‐latitude Holocene hydroclimate derived from lake sediment flux and geochemistry - Adrian G. Parker; Gareth W. Preston; Ash Parton; Helen Walkington; Phillip E. Jardine; Melanie J. Leng; Martin J. Hodson (Journal of Quaternary Science, 2016)
This study investigates hydrological responses to climatic shifts using sediment flux data derived from two dated palaeolake records in south‐east Arabia. Flux values are generally low during the early Holocene humid period (EHHP) (∼9.0–6.4k cal a BP) although several short‐lived pulses of increased detrital input are recorded, the most prominent of which is dated between ∼8.3 and 7.9k cal a BP. The EHHP is separated from the mid‐Holocene humid period (MHHP) (∼5.0–4.3k cal a BP) by a phase of increased sediment flux and aridity, which began between ∼6.4 and 5.9k cal a BP and peaked between ∼5.2 and 5.0k cal a BP. The termination of the MHHP is marked by a phase of high detrital sediment flux between ∼4.3 and 3.9k cal a BP. While long‐term shifts in climate are most likely linked to changes in the summer position of the Intertropical Convergence Zone and associated Indian and African monsoon systems, it is noted that the abrupt, short‐term phases of aridity observed in both records are coeval with intervals of rapid climate change globally, which triggered non‐linear, widespread landscape reconfigurations throughout south‐east Arabia.